Effect of Pacifier Design on Nonnutritive Suck Maturation and Weight Gain in Preterm Infants: A Pilot Study - Alexander Ziegler, DDS; Jill L. Maron, MD; Steven M. Barlow, PhD; Jonathan M. Davis, MD (Elsevier, 2020)
ABSTRACT: Background: Pacifiers are effective in promoting oral feeding by increasing the maturation of nonnutritive sucking to nutritive suck in preterm neonates. It is unclear whether pacifier design can influence suck dynamics and weight loss during the first week of life. Objectives: This pilot study examined the feasibility of studying the effect of pacifier design on suck maturation and weight loss in preterm neonates. Methods: Twenty-five preterm neonates (mean [SD] birth weight 1791 [344.9] grams, mean [SD] gestational age 33.1 [1.2] weeks) were studied in a single newborn intensive care unit. Neonates were assigned to either an orthodontic pacifier (n = 13) or a bulb-shaped pacifier (n = 12) immediately after birth. Suck dynamics (cycles per minute, total compressions per minute, cycle bursts, and amplitude) were assessed with an NTrainer (Innara Health, Olathe, Kansas). Weight was recorded during the first week of life on day 1.2 (±2.5 days) and day 6.0 (±2.1 days). Descriptive statistics were applied to analyze data. Results: No significant differences were seen between groups with respect to birth weight and gestational age. Reproducible nonnutritive sucking measurements could be obtained with the NTrainer, with both types of pacifiers. No differences were detected in nonnutritive sucking dynamics or weight loss over time within each group or between groups. Conclusions: Data indicate that it is feasible to measure nonnutritive sucking dynamics and associated weight loss in relation to pacifier design in preterm neonates. Larger trials over longer time periods are needed to determine whether pacifier design influences suck dynamics and maturation, oromotor function, feeding/weight loss, and dental formation in preterm neonates. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)